Administrative and Financial Reforms in Nigeria: The Panacea for Efficient Service Delivery - Gbosien Chris Sokoh; Ugo Chuks Okolie (Universitas Medan Area, 2023)
The study examines the Nigerian government's administrative and financial reforms. The goal is to examine the impact of various Programs and policies implemented in Nigeria, as well as the influence of these reforms on the country's public sector. This is critical in light of the evident professional shift among government and personnel on the one hand and among professionals on the other. In doing the research, this publication used an exploratory approach. The study's findings show that there is a lot of literature on public sector reorganization, but there isn't much on administrative and financial reform Programs in the public sector. As a result, the study suggests that reform Program is critical to guaranteeing efficient service delivery in the Nigerian public sector and national growth. The study suggests that government Programs and policies be reviewed on a regular basis to ensure alignment with national goals, mobilization of necessary resources for Program execution and implementation, and coordination among all levels of government and professionals.